Risk of recurrence after endoscopic resection of nonpedunculated T1 colorectal cancer - Arthursson, Victoria; Medic, Selma; Syk, Ingvar; Rönnow, Carl-Fredrik; Thorlacius, Henrik (Endoscopy, 2022)
Background The long-term outcome after local excision of T1 colorectal cancer (CRC) remains unknown. The aim of this study was to examine clinical and histopathological risk factors for recurrence in patients with T1 CRC undergoing endoscopic resection.Methods This was a retrospective registry-based population study on prospectively collected data of all patients with nonpedunculated T1 CRC undergoing only local excision (no salvage surgery) in Sweden between 2009 and 2018. Potential risk factors for recurrence, including age, sex, tumor location, resection margins, lymphovascular, perineural, and submucosal invasion, grade of differentiation, and mucinous subtype, were analyzed using univariate and multivariate cox regression.Results Median follow-up time was 60 months, and 28 /602 patients (4.7 %) had a recurrence (13 local and 18 distant). Recurrence rate stratified by submucosal invasion was: Sm1 3.5 % (14 /397), Sm2 6.0 % (8 /133), and Sm3 8.3 % (6 /72), with no significant differences. Resection margins, lymphovascular and perineural invasion, grade of differentiation, mucinous subtype, and age were not significant risk factors for recurrence. In contrast, rectal location was found to be a significant risk factor for tumor recurrence in multivariate analysis (hazard ratio 3.08, P = 0.006). The 3– and 5-year disease-free survival was 96.2 % and 91.1 %, respectively, in T1 CRC patients undergoing endoscopic resection.Conclusion Tumor recurrence was rare (4.7 %) in this large population-based study on recurrence after local excision of nonpedunculated T1 CRC. Rectal location was an independent risk factor for recurrence, suggesting the need for strict surveillance after endoscopic resection of early rectal cancer.